A política de distribuição da verba publicitária do governo federal no Brasil (2000/2014) - Santos, Pedro Alexandre de Oliveira (2018)
The communication policy of the Brazilian State, based on the distribution of advertising dollars or federal media funds, in parts, consists of the amount of public resources destined to the purchase of advertising space in the different media and communication vehicles in the country, in order to advertise institutional framework of government. The distribution of this amount of media is usually directed to the industrial communication system formed by the national broadcasting network, which in turn is responsible for a large portion of the commercialization of the merchandise audience produced under the aegis of the Cultural Industry during the development of the monopoly capitalism. The absence of papers that deepen the discussion about the links between federal advertising and the oligopolistic market of communication have led us to question in what sense the Federal Government, when becoming a buyer of the merchandise audience contributes to the maintenance of the oligopolistic communication market in the country ? Our hypothesis is that the Federal Government, as advertiser and buyer of the merchandise audience, contributes to the maintenance of the oligopolistic communication market, to the detriment of the public system. The present work has the objective of analyzing the historical, economic and political aspects that support the policy of distribution of the advertising budget of the Federal Government, as well as its location in the communication circuit fed by the Cultural Industry in Brazil. The methodology used belongs to the Critical Studies of the Political Economy of Communication (EPC), and articulates the analysis of quantitative data referring to the amount of media funding distributed to the media, offered by the Federal Government from 2000 to 2014, with the research (2000 and 2004), Valério Britos (2000), Dallas Smythe (2000), and the Brazilian Institute of Public Information (IAP), and the range of national and international bibliographical references, based on studies by César Bolaño (2000 and 2004). 1977), Celso Furtado (2005) and Maria Arminda (2015). It is hoped that this research will contribute to the advancement of critical knowledge in the area of the EPC and present tools for future analysis on the subject in question.